New Social Accounting Matrix for Jordan: A 2015 Nexus project Social Accounting Matrix - Raouf, Mariam; Randriamamonjy, Josee; Elsabbagh, Dalia; Wiebelt, Manfred (International Food Policy Research Institute, 2021)
This new Social Accounting Matrix (SAM) for Jordan is a snapshot representation of the Jordanian economy in which productive activities, factors of production, and economic transactions between the main agents, including households, government, and the rest of the world, are illustrated in a circular flow. It has been constructed using IFPRI's Nexus format, which uses common data standards, procedures, and classification systems for constructing and updating national SAMs. This new SAM for Jordan is expected to be an important dataset for the Arab (Agricultural) Investment for Development Analyzer (AIDA), which is tool based on computable general equilibrium (CGE) model analyses. AIDA was developed to inform national and regional development strategies by providing evidence on the impact of agricultural investments on economic development.